Inheritance of The Lip Print Pattern as A Means of Identification in The Case of Cleft Lip and Palate - An'nisaa Chusida; Arofi Kurniawan; Mohammad Denis Solikhin; Mayang Sarumpun Mangurai; Michael Saelung; Beta Novia Rizky; Beshlina Fitri W. R Prakoeswa (Jurnal Kesehatan Gigi, 2022)
Lip prints are wrinkle patterns and grooves on the mucosal surface of the lips. Just like fingerprints, every individual in this world has their own unique lip prints patterns. According to the previous studies, the parents of cleft lip and palate (CL/CP) patients have certain lip print patterns. As a result, the lip print pattern can provide information on the inheritance of CL/CP. This review aims to explore the potential of lip print patterns as a means of identification in the inheritance of cleft lip and palate. The online literature search in the PubMed database, Science Direct, and Google Scholar was conducted with a combination of the following keywords: “lip prints”, “cleft lip/palate suffer”, “lip print classification”, and “cleft lip/palate prints”. In addition to online literature searches, reference lists from all the included articles were manually examined for further full-text studies. This review included research and review articles published during the last 10 years period (2012-2022). The result showed that there were 7 articles that met the inclusion criteria. In conclusion, various studies explained that the lip prints pattern type II and whorl/O are the most observed in the inheritance of CL/CP.